No small matter: emerging roles for exosomal miRNAs in the immune system. (19th June 2021) - Bauer, Kaylyn M.; Round, June L.; O'Connell, Ryan M.
Abstract : Extracellular communication is critical to the function of an organism. Exosomes, small lipid extracellular vesicles, have been recently appreciated to participate in this vital function. Within these vesicles lie critical bioactive molecules including mRNAs, proteins, and a plethora of noncoding RNAs, including microRNAs (miRNAs). Exosomal miRNAs have been shown to be produced by, trafficked between, and function in many distinct donor and recipient cell types, including cells of the immune system. For instance, loss of these critical communicators can alter the cellular response to endotoxin, and when tumor cells lose the ability to secrete these vesicles, the immune system is able to effectively suppress tumor growth. This review will highlight key findings on the known communication to and from the immune system, highlighting exosomal miRNA research in macrophages, dendritic cells, B lymphocytes, and T cells. Additionally, we will focus on three major areas of exosomal studies that involve immune responses including mucosal barriers, adipose tissue, and the tumor microenvironment. These environments are heterogeneous and dynamic, and rapidly respond to the microbiota, metabolic shifts, and immunotherapies, respectively. It is clear that exosomal miRNAs play pivotal roles in regulating cross‐talk between cells in these tissues, and this represents a novel layer of cellular communication proving critical in human health and disease. Abstract : Cell–cell communication via extracellular vesicles, including exosomes, is critical to the function of mammalian organisms. We review recent advances in our understanding of extracellular miRNA transfer via exosomes, within the immune system and three tissue niches rich with immune cells: adipose tissue, the intestinal compartment, and the tumor microenvironment.